Empirical estimates of the Galactic halo contribution to the dispersion measures of extragalactic fast radio bursts using X-ray absorption. Issue 1 (28th October 2020) - Das, Sanskriti; Mathur, Smita; Gupta, Anjali; Nicastro, Fabrizio; Krongold, Yair
ABSTRACT: We provide an empirical list of the Galactic dispersion measure (DMGal ) contribution to the extragalactic fast radio bursts (FRBs) along 72 sightlines. It is independent of any model of the Galaxy, i.e. we do not assume the density of the disc or the halo, spatial extent of the halo, baryonic mass content, or any such external constraints to measure DMGal . We use 21-cm, UV, EUV, and X-ray data to account for different phases, and find that DMGal is dominated by the hot phase probed by X-ray absorption. We improve upon the measurements of N ($\rm{O}\, {\small VII}$ ) and f $_{\rm O\, {\small VII}}$ compared to previous studies, thus providing a better estimate of the hot phase contribution. The median DMGal = 64$^{+20}_{-23}$ cm −3  pc, with a 68 per cent (90 per cent) confidence interval of 33–172 (23–660) cm −3  pc. The DMGal does not appear to follow any trend with the Galactic longitude or latitude, and there is a large scatter around the values predicted by simple disc + spherical halo models. Our measurements provide more complete and accurate estimates of DMGal independent from the previous studies. We provide a table and a code to retrieve DMGal for any FRB localized in the sky.